Single digit attrition rates in information technology industry in Kerala - Strength or weakness? - A narrative enquiry - Cheeran, Maria T.; Moolakkattu, John S. (2013)
Perceiving the Information Technology (IT) potential employment, Kerala has invested a lot of money in government sector and also in public-private partnership mode in developing IT industry enabling Keralites to work from Kerala. Attrition in IT industry in cities such as Bangalore, Chennai, Pune were reported to be high while the attrition in Kerala maintained a single digit. This article makes a critical analysis on this interesting phenomenon. Narrative informal and semi structured interview approach is adopted for this research. The study leads to the inference that the reason for the low attrition rate is the lack of opportunities for employment in Kerala and not the employment friendly Human Resource (HR) policies. The tactics played by the employers to lower the attrition have already affected the credibility of companies in Kerala in the job market. Some pragmatic suggestions proposed to make the state a favourite of lT Employee 's choice which becomes imperative to keep Kerala as an employer's choice. "For the growth and success in business and trade, what is needed is a creative leader. Who is the creative leader? Creative leadership means exercising the vision to change the traditional role from the commander to the coach, manager to mentor, from director to delegator and from one who demands respect to one who facilitates self-respect." - Reproduced.
Keywords: Information technology